The Effect of Paired Passing Training on the Lower Passing Ability - Yulda Nikodemus Manurung; Dewi Maya Sari (Journal of Football Research, 2024)
This study aims to determine the effect of paired passing exercises on the lower passing ability of Bintang Junior soccer school students aged 10-12 years. The type of research is experimental with the design "The One Group Pretest Posttest Design". The research population was Bintang Junior SSB students, aged 10-12 years, totaling 27 people. The instrument used was the low ball passing test from Subagyo Irianto (1995: 9) with a validity of 0.812 and a reliability of 0.856. Data analysis used t test with 5% significance level. The results showed that there was a significant effect of paired passing training on the lower passing ability of Bintang Junior soccer school students aged 10-12 years, with a t value of 6.574> t table 2.09, and a significance value of 0.000 <0.05, and a percentage increase of 37.69%. Based on the analysis of research results, it can be concluded that there is a significant influence of pair passing training on the bottom passing ability of Bintang Junior football school students aged 10-12 years.